Building a Halal Tourism Resilience Index: A Multi-Destination Study in South Sulawesi - Sirajuddin Sirajuddin; A Syathir Sofyan; Shafinar Ismail; Andi Vira Yulianti (UPT Publikasi Ilmiah UNISBA, 2026)
This study developed and evaluated the Halal Tourism Resilience Index (HTRI) across various destination types in South Sulawesi, Indonesia. The paper employed the AHP method, involving three tourism experts, to identify 15 destinations in South Sulawesi. The study identified key patterns of resilience performance. The results showed that religious and cultural destinations demonstrated the highest resilience, supported by strong Islamic identity and leadership, while natural and man-made destinations demonstrated moderate resilience, limited by physical infrastructure and gaps in disaster preparedness. Meanwhile, educational and community-based destinations recorded the lowest resilience, largely due to limited institutional coordination and low economic capacity. The AHP findings highlighted that the Islamic Tourism Identity Sustainability dimension had the greatest influence (0.38), followed by Economic Vulnerability and Islamic Trauma Healing (0.17). Further quadrant analysis revealed that the level of resilience was not always proportional to the number of tourists, but inversely related to disaster exposure. The implications of the study suggest that enhancing Islamic governance, integrating disaster management, and strengthening value-based leadership are crucial for maintaining the resilience of the halal tourism system in Indonesia.